Back-Translation as Self-Translation: The Strange Case of Darkness at Noon. (November 2020) - Gaskill, Howard
Abstract : This article is a response to the recent discovery in manuscript of the lost German version of Koestler's best-known novel, now published as 'the' original. The circumstances surrounding the production of that MS, together with Daphne Hardy's English translation, are examined. It is shown that over half of Koestler's later 'back-translation' from English is in fact based on a version of the German that pre-dates the MS, and that this itself post-dates Hardy's Darkness. Moreover, Koestler regarded himself as 'co-translator' of the English and seemed prepared to concede priority to Hardy's (and his) version over his own re-worked German. In the light of this, the notion of a single stable original of the novel may be called into question. The essay makes use of research conducted in the Koestler Archives in Edinburgh, and also of scanned copy of the German manuscript.